Implementasi Obyek Grafis 3-D dengan POV-Ray - Rudy Hartanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
The development of 3-D graphics applications leads to the generation of photo-realistic graphics image, which is implemented many applications, such us design, simulation, games as well as to making animated films. Rendering techniques used to generate the graphics image is still les realistic, because lack of real-world lighting models. Subsequent research led to the global illumination models that used a model of the light rays as in the actual physical environment. The algorithm that can implement global illumination models are ray-tracing algorithm. This algorithm is capable of producing 3-D graphic image of a high quality photo-realistic, but requires a complex mathematical equation and computation. POV-Ray is a tool used to implement the ray-tracing models to produce photo-realistic graphics image. These results show that the POV-Ray can generate 3-D graphic image of high qualityt.